Experiências adversas na infância das mães e a correlação com o vínculo materno de crianças assistidas numa instituição de primeira infância - Menescal, João Vicente (2018)
The idea of facts experienced in early childhood can influence the health and psychosocial condition in adult life is an episteme of current science. Such childhood experiences can be either favorable or adverse. This study aims to estimate the association between adverse experiences in the mothers' childhood and the abilities / capacities in the maternal bond with their children at the age of 0 to 5 years and 11 months. The present cross - sectional study consisted of a single interview with the application of standardized questionnaires, with the (biological) mothers of children assisted in an institution.The evaluation of the data collected used statistical tests to ascertain significant associations between the variables adverse experiences in the mothers' childhood and abilities / capacities in the maternal bond. Significant associations were found between the number of adverse experiences in the mothers' childhood and the abilities / capacities related to the maternal bond in the aspects of control and pressure in the maternal social role. The study refers to the importance of dialogue between mothers and children, to minimize the interference of adverse experiences in childhood to the adult life of the child.